COVID-19 epidemiology and changes in health service utilization in Uganda's refugee settlements during the first year of the pandemic - Chiara Altare; Natalya Kostandova; Jennifer OKeeffe; Emmanuel Omwony; Ronald Nyakoojo; Julius Kasozi; Paul B. Spiegel (BMC, 2022)
Abstract Background The COVID-19 pandemic has been characterized by multiple waves with varying rates of transmission affecting countries at different times and magnitudes. Forced displacement settings were considered particularly at risk due to pre-existing vulnerabilities. Yet, the effects of COVID-19 in refugee settings are not well understood. In this study, we report on the epidemiology of COVID-19 cases in Uganda's refugee settlement regions of West Nile, Center and South, and evaluate how health service utilization changed during the first year of the pandemic. Methods We calculate descriptive statistics, testing rates, and incidence rates of COVID-19 cases in UNHCR's line list and adjusted odds ratios for selected outcomes. We evaluate the changes in health services using monthly routine data from UNHCR's health information system (January 2017 to March 2021) and apply interrupted time series analysis with a generalized additive model and negative binomial distribution, accounting for long-term trends and seasonality, reporting results as incidence rate ratios. Findings The first COVID-19 case was registered in Uganda on March 20, 2020, and among refugees two months later on May 22, 2020 in Adjumani settlement. Incidence rates were higher at national level for the general population compared to refugees by region and overall. Testing capacity in the settlements was lower compared to the national level. Characteristics of COVID-19 cases among refugees in Uganda seem to align with the global epidemiology of COVID-19. Only hospitalization rate was higher than globally reported. The indirect effects of COVID-19 on routine health services and outcomes appear quite consistent across regions. Maternal and child routine and preventative health services seem to have been less affected by COVID-19 than consultations for acute conditions. All regions reported a decrease in consultations for respiratory tract infections. Interpretation COVID-19 transmission seemed lower in settlement regions than the national average, but so was testing capacity. Disruptions to health services were limited, and mainly affected consultations for acute conditions. This study, focusing on the first year of the pandemic, warrants follow-up research to investigate how susceptibility evolved over time, and how and whether health services could be maintained.